Mindfulness-Based Emotional Regulation in a Woman With Schizophrenia in an Indonesian Social Rehabilitation Facility: A Structured Case Study - Wibhowo, Christin; Dewantara, Irene Kurnia (International Journal Labs, 2026)
Schizophrenia is a chronic psychotic disorder characterized by distortions in perception, emotions, and behavior, and has the potential to cause social functioning disorders. This study aims to explore the effectiveness of a Mindfulness-Based Emotional Regulation intervention in reducing emotion dysregulation and enhancing affective stability in a woman with schizophrenia residing in a social rehabilitation facility. The research uses a case study approach with data collection techniques through interviews, participant-structured observations, and psychological tests (Wartegg, graphic test, and PANAS). The results of the assessment showed that the client experienced visual hallucinations, delusions, high anxiety, and difficulty regulating emotions, but had adequate activity motivation and cognitive ability. Mindfulness interventions that include progressive relaxation, art activities, and drawing occupations are used to increase emotional awareness and lower anxiety. The results suggest that the mindfulness intervention contributed to enhanced emotional regulation in a woman with schizophrenia living in an Indonesian social rehabilitation facility. The Wong-Baker Faces Pain Rating Scale reflected decreased internal discomfort and improved affective stability following the intervention.